Calcium Oxide Decomposed From Chicken’s and Goat’s Bones as Catalyst For Converting Discarded Cooking Oil to be Biodiesel - Aldes Lesbani; Yosine Susi; Marieska Verawaty; Risfidian Mohadi (Aceh International Journal of Science and Technology, 2015)
Thermal decomposition of calcium oxide from chicken’s (Gallus gallus domesticus) and goat’s (Capra Hircus Aegragus) bones was prepared at temperature variations of 400, 500, 800, 900, 1000, and 1100 oC respectively. X-ray diffractometer (XRD), FT-IR and SEM were used for calcium oxide characterization. XRD diffraction pattern of the bone’s after thermal decomposition at 1100oC has similarity to the XRD standard diffraction pattern from Joint Committee on Powder Diffraction Standard (JCPDS). Diffractions of 2q values being used are 34.2o, 37.3o, 58.3o, 64.1o, and 67.3 o.  Ca-O presence in the samples was detected by FT-IR characterization at wavenumber of 354,90 cm-1. SEM profile show reducing size of bones after decomposition in both chicken’s and goat’s bones. Furthermore, the prepared calcium oxide was applied for biodiesel synthesis from discarded cooking oil through transesterification reaction. By applying the catalysts decomposed from chicken’s and goat’s bones, the biodiesel product showed characteristics as follows: biodiesel applied the chicken’s bone catalyst has fatty acid number of 0.56 mg/KOH, iod number of 22.41 g I2/100 g KOH, density of 0.88 g/cm3 and viscosity of 5.91 mm2/s, while biodiesel applied the goat’s bone catalyst has 0.56 mg/KOH, iod number of 21.57 g I2/100 g KOH, density of 0.88 g/cm3 and viscosity of 6.34 mm2/s. Those biodiesel’s characteristic values meet the National Standard of Indonesia (SNI) for biodiesel.